(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the primary concerns within cognitive linguistics, a field that examines the interplay between language and human cognition. Key issues include the nature of meaning, the embodiment of language, the role of metaphor, and the interaction between language and thought. By analyzing these topics with examples, the article sheds light on the fundamental questions and debates shaping cognitive linguistics today.